On the importance of investigating CME complexity evolution during interplanetary propagation - Winslow, Réka M.; Scolini, Camilla; Jian, Lan K.; Nieves-Chinchilla, Teresa; Temmer, Manuela; Carcaboso, Fernando; Schmieder, Brigitte; Poedts, Stefaan; Lynch, Benjamin J.; Wood, Brian E.; Palmerio, Erika; Lugaz, Noé; et al. (Frontiers in Astronomy and Space Sciences, 2022)
This perspective paper brings to light the need for comprehensive studies on the evolution of interplanetary coronal mass ejection (ICME) complexity during propagation. To date, few studies of ICME complexity exist. Here, we define ICME complexity and associated changes in complexity, describe recent works and their limitations, and outline key science questions that need to be tackled. To advance our fundamental understanding of CME complexity evolution, our main recommendations to the heliophysics community are: 1) Prioritize spacecraft missions that can obtain comprehensive in situ ICME measurements at multiple heliocentric distances in the inner heliosphere. 2) Explore options, through simulations, for optimal spacecraft configuration in terms of radial, longitudinal, and latitudinal spacing to achieve the necessary spatial resolution to fully investigate the evolution of ICME complexity. 3) Once the data are available, focus efforts on comprehensive/holistic studies of ICME complexity evolution, integrating results from many vantage points. Fundamental research on ICME complexity changes from the solar corona to 1 AU and beyond is critical to our physical understanding of the evolution and interaction of transients in the inner heliosphere. Furthermore, a comprehensive understanding of such changes is required to understand the space weather impact of ICMEs at different heliospheric locations and to improve on predictive space weather models.